Secukinumab, a human anti-IL-17A monoclonal antibody, for moderate to severe Crohn's disease: unexpected results of a randomised, double-blind placebo-controlled trial. - Hueber, W; Sands, B; Lewitzky, S; Vandemeulebroecke, M; Reinisch, W; Higgins, P; Wehkamp, J; Feagan, BG; Yao, MD; Karczewski, M; Karczewski, J; Pezous, N; et al. (2012)
OBJECTIVE: The authors tested whether the anti-interleukin (IL)-17A monoclonal antibody secukinumab was safe and effective for the treatment of active Crohn's disease. DESIGN: In a double-blind, randomised, placebo-controlled proof-of-concept study, 59 patients with moderate to severe Crohn's disease (Crohn's Disease Activity Index (CDAI) ≥220 to ≤450) were assigned in a 2:1 ratio to 2×10 mg/kg intravenous secukinumab or placebo. The primary end point, addressed by bayesian statistics augmented with historical placebo information, was the probability that secukinumab reduces the CDAI by ≥50 points more than placebo at week 6. Ancillary analyses explored associations of 35 candidate genetic polymorphisms and faecal calprotectin response. RESULTS: 59 patients (39 secukinumab, 20 placebo, mean baseline CDAI 307 and 301, respectively) were recruited. 18/59 (31%) patients discontinued prematurely (12/39 (31%) secukinumab, 6/20 (30%) placebo), 10/59 (17%) due to insufficient therapeutic effect (8/39 (21%) secukinumab, 2/20 (10%) placebo). Fourteen serious adverse events occurred in 10 patients (seven secukinumab, three placebo); 20 infections, including four local fungal infections, were seen on secukinumab versus none on placebo. Primary end point analysis estimated <0.1% probability (CDAI (SD) =33.9 (19.7), 95% credible interval -4.9 to 72.9) that secukinumab reduces CDAI by ≥50 points more than placebo. Secondary area under the curve analysis (weeks 4-10) showed a significant difference (mean ΔCDAI=49; 95% CI (2 to 96), p=0.043) in favour of placebo. Post hoc subgroup analysis showed that unfavourable responses on secukinumab were driven by patients with elevated inflammatory markers (CRP≥10 mg/l and/or faecal calprotectin≥200 ng/ml; mean ΔCDAI=62; 95% CI (-1 to 125), p=0.054 in favour of placebo). Absence of the minor allele of tumour necrosis factor-like ligand 1A was strongly associated with lack of response measured by baseline-adjusted changes in calprotectin at week 6 (p=0.00035 Bonferroni-corrected). CONCLUSIONS: Blockade of IL-17A was ineffective and higher rates of adverse events were noted compared with placebo. CLINICAL TRIAL REGISTRATION: This trial was registered at ClinicalTrial.gov with the number NCT01009281.